2010
DOI: 10.21608/jvmr.2020.77591
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies on Listeriosis in sheep

Abstract: This study was carried out in El-Dakahilia governorate on six flocks at different areas 2448 sheep located with varied ages and with history of nervous manifestation. The Prevalence of nervous manifestations was 4.9% (105 /2448). The case fatality rate and mortality rate were 77.14 % and 3.3 % respectively. The percent of Listeria monocytogenes was 26.66% (8/30). Examination of CSF of diseased and control healthy sheep revealed significance elevation of total cell count, total protein and creatinine cytokinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…The variations in clinical manifestations of the disease are attributed to the site affected in nervous system (medulla, pons, cerebellum, cerebrum or anterior spinal cord) and impairment of cranial nerves (Brugere-Picoux. 2008;Younis et al, 2010). The histopathological lesions observed in this study are in conformity to previous observations by Hamidi et al, (2020) and Kumar et al, (2007) where marked perivascular cuffing comprising of mononuclear cells, polymorphonuclear leukocytes forming abscesses and congested meninges with infiltration of mono nuclear cells were evidenced.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The variations in clinical manifestations of the disease are attributed to the site affected in nervous system (medulla, pons, cerebellum, cerebrum or anterior spinal cord) and impairment of cranial nerves (Brugere-Picoux. 2008;Younis et al, 2010). The histopathological lesions observed in this study are in conformity to previous observations by Hamidi et al, (2020) and Kumar et al, (2007) where marked perivascular cuffing comprising of mononuclear cells, polymorphonuclear leukocytes forming abscesses and congested meninges with infiltration of mono nuclear cells were evidenced.…”
Section: Discussionsupporting
confidence: 92%
“…This was a severe outbreak indicated by a high case fatality rate which was in line with a previous report by Younis et al, (2010). Despite the low mortality in the entire population, significantly high mortality rate was observed in goats above one year of age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All affected sheep more than 1-year-old [17]. On the other hand, young animals can be frequently affected when they are losing and changing their teeth, which leads to lesions in the gums that the bacteria can penetrate [20]. In the present report, the age of the sheep ranged from 5 to 6 months.…”
Section: Discussionmentioning
confidence: 63%
“…This suggests that the disease depends on more the environmental conditions than on the age of the animals. In sheep of up to 6-month-old, it was observed that nervous manifestations of listeriosis are more pronounced than in adult animals [20], and the lethality rate was significantly higher when compared to that in sheep older than 6 months [9].…”
Section: Discussionmentioning
confidence: 93%